A block-chain excellency in the mining of crypto currency. Issue 1 (2nd January 2022) - Kumar, Pawan; Reshma,; Sharma, Kamal Kant; Gandhar, Abhishek
Abstract: Bitcoin is the most prevalent out of several crypto currencies in operation which was launched in 2009. Its value has been increased to such an extent that it has reached 19.7 Billion USD by January 2018 (Statista 2018). As the pricing of Bitcoin rose day by day various terrorist group and illegal organization are using the crypto currency to finance their terror activities around the world through by passing the legal mechanism of banking system. This study is an effort to understand the mechanism of crypto currencies mining. This study will give a clear perspective about the risks involved in the mining of crypto currency. It also presented the methodology of mining the crypto currency. This study can be an eye-opener for some new entrants in area of crypto currency, on the other hand it can attracts many researchers to invade this field.